Immediate and Delayed Effect of an Integrated Literacy-Numeracy Remediation Program - Guray, Jomar (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the effectiveness of an Integrated Literacy-Numeracy Remediation Program in improving the literacy and numeracy performance of Grade 7 learners at Maujao National High School. The study was anchored on Vygotsky’s Sociocultural Theory, Bruner’s Constructivist Theory, Sweller’s Cognitive Load Theory, and the Input-Process-Output-Feedback (IPOF) framework. A quantitative quasi-experimental one-group pretest-posttest design was employed involving 69 Grade 7 learners identified with literacy and numeracy difficulties through the Philippine Informal Reading Inventory (PHIL-IRI) and Rapid Mathematics Assessment (RMA). Data were collected using standardized assessment tools and an integrated remediation program that incorporated explicit instruction, guided practice, contextualized learning activities, and formative assessment. Results showed that learners initially exhibited substantial literacy and numeracy deficiencies, with most participants classified at the frustration level in literacy and at the emerging or non-proficient level in numeracy. Session-based monitoring demonstrated consistent improvements in reading fluency, comprehension, and numeracy skills throughout the intervention period. Post-test findings revealed notable gains in both literacy and numeracy performance, with learners progressing from lower proficiency levels to instructional, independent, developing, and transitioning categories. The Wilcoxon Signed-Rank Test further indicated statistically significant differences between pre-test and post-test scores in word reading, comprehension, and numeracy, confirming the effectiveness of the intervention. The study concluded that the Integrated Literacy-Numeracy Remediation Program effectively reduced foundational learning gaps and supported learner achievement through structured and contextualized instruction. It recommends the continued implementation and institutionalization of integrated remediation programs supported by ongoing assessment, teacher capacity-building, and evidence-based instructional practices. The study aligns with Sustainable Development Goal (SDG) 4 on Quality Education and SDG 8 on Decent Work and Economic Growth by strengthening foundational learning and promoting educational equity. It contributes to educational, institutional, and socio-economic sustainability through improved learning recovery initiatives and enhanced opportunities for learner development.